Human papillomavirus DNA and mRNA prevalence and association with cervical cytological abnormalities in the Irish HIV population. (October 2015) - Loy, Aisling; McInerney, Jamie; Pilkington, Loretto; Keegan, Helen; Delamere, Sandra; Martin, Cara M; Sheils, Orla; O'Leary, John J; Mulcahy, Fiona
The complex interplay between HIV and human papillomavirus and its link to cervical dysplasia is poorly understood. This is the first study to assess the prevalence of oncogenic human papillomavirus mRNA in HIV-positive women, its relationship to HIV and its potential use in the triage of cervical cancer screening in HIV-positive women. In this cross-sectional study, we included 321 HIV-positive women. In all, 28.7% had abnormal cervical cytology, 51.1% were human papillomavirus DNA-positive and 21.8% tested positive for human papillomavirus mRNA. Women with a CD4 count of <200 × 10 6 /L were more likely to test positive for human papillomavirus DNA and mRNA. Virally suppressed women were less likely to be human papillomavirus DNA-positive; however, the same did not hold true for human papillomavirus mRNA. We found the human papillomavirus mRNA screening to be more specific when screening for low-grade squamous intraepithelial lesion and high-grade squamous intraepithelial lesion than human papillomavirus DNA at 84.53% compared to 57.36%. However, the sensitivity was less at 51.59% versus 91.07% for human papillomavirus DNA. It may be possible in the future to use human papillomavirus mRNA/DNA testing within a triage algorithm for the screening and management of cervical cancer in the HIV-positive patient.